2021
DOI: 10.1002/cpe.6379
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging big data in smart cities: A systematic review

Abstract: Recently, the notion of a smart city, which includes smart well‐being, smart transit, and smart society, has attracted much attention due to its impact on people's quality of living. Data in smart cities are characterized by variety, velocity, volume, value, and veracity that are the well‐known characteristics of big data. The fast pace expanding of IoT devices and sensors in smart cities generates a huge volume of data that can help decision‐makers and managers in city management. The aim of this article is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 132 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…First, a comprehensive search of two databases, the WoS Core Collection and the IEEE Xplore database, was conducted. To identify relevant articles, we drew on the search criteria set out by Karimi et al (2021): TS=(('big data' AND 'smart' AND ('cities' OR 'city')).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, a comprehensive search of two databases, the WoS Core Collection and the IEEE Xplore database, was conducted. To identify relevant articles, we drew on the search criteria set out by Karimi et al (2021): TS=(('big data' AND 'smart' AND ('cities' OR 'city')).…”
Section: Methodsmentioning
confidence: 99%
“…The definitions of smart cities were summarized by Hajek et al (2022), who concluded that the smart city relies on ICT capability that improves resource efficiency, facilitates transportation, affects people, increases living standards, and promotes prosperity and sustainability. The rise of smart cities is an outstanding illustration of the diffusion and utilization of big data analytics (Karimi et al, 2021).…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…In a study for quantification of instantaneous drive cycle and parameters in high spatio-temporal data, a novel approach was enabled by the authors in [23] which provided the basis for a microscopic emissions model. In an article by [24], where efforts were made using a novel algorithm and architecture to handle big data in smart cities. In a study by [25], several taxis data were decimated to find out why a taxi driver declines to serve taxi customers in Bangkok using an approach that is data driven for taxi probe data and their collection, analysis was carried out for several months.…”
Section: Related Workmentioning
confidence: 99%